Bioviability of Beta-Tricalcium Phosphate (Î²-TCP) Nanoencapsulation from Synthesis of Anadara granosa Shells on Fibroblast Cell Line BHK-21 Cell Culture - Aprilia,; Sri Kunarti,; Indah Budhy S , Theresia; Parwati Sari , Rima (International Journal of Integrated Engineering, 2022)
The purpose of this research is to measure the toxicity of beta-tricalcium Phosphate (Î²-TCP) nanoencapsulation resulting from 18 hours of hydrothermal process on Anadara granosa shell and 3 hours of# sintering. The encapsulation process is carried out to reduce side effects and toxic effects and to inhibit the speed of calcium solubility, which can prevent tunnel effects. Results: Cell viability data, analysed using the One Way ANOVA statistical test, show there is no significant difference between the A. granosa shell encapsulation processes with treatment groups of 1, 2, 3, 4, 5 and 6 hours. The highest viability occurred in Treatment Group 2, with an A. granosa shell encapsulation stirrer process of 2 hours. Conclusion: A. granosa clam shell nanoencapsulation is proved to be non-toxic and can be used in dentistry therapy.